Pelatihan Kemampuan Perserta Didik SMA Islam Az-Zahrah Palembang Dalam Mengindentifikasi Unsur Intrinsik Film Pendek “ Sekawan Limo” Melalui Media YouTube - Mawarni Mawarni; Emawati Emawati (Jurnal Masyarakat Mengabdi Nusantara, 2024)
This research aims to improve the ability of students at Az-Zahrah Islamic High School Palembang in recognizing the intrinsic elements of the short film entitled "Sekawan Limo" using YouTube as a medium. By taking advantage of advances in information technology, it is hoped that students can take advantage of digital platforms as an efficient learning tool. This training activity involves the introduction of intrinsic elements such as themes, characters, plots, settings, perspectives, and messages. The methodology used during the training includes initial tests, teaching material, watching movies, discussions, and assessments. The findings of this study show that there is an increase in students' understanding of the intrinsic elements of film after participating in training. The use of YouTube as a learning tool was declared effective in improving students' analytical skills.